PARAMETER STUDY OF STABLE WALKING GAITS FOR NAO HUMANOID ROBOT - Mohd Shaari Azyze, Nur Latif Azyze; Razali, Muhammad Razmi; Md Isa, Ida Syafiza; Miskon, Muhammad Fahmi (Sun Publication, 2013)
It is a challenge to any researcher to maintain the stability of the robot while in the walking motion. This paper proposes for parameter study of a walking pattern method which is inspired by the Dip Goswami (2009). The walking pattern is generated based on three points. These points are located at ankle left and right and one at the hip of the NAO humanoid robot. By using these points the walking gaits are generated to use as a reference point while walking motion. Then, an inverse kinematics with geometric solution of a ten degree-of-freedom humanoid robot is formulated from hip until the ankle joint. By sampling period of time with ten this reference point is used to find the joint angle of each link. The NAO humanoid robot is built in with force resistive sensor (FSR) located under both feet are used to determine the walking stability by using force distributer concept. The zero moment point of the robot is calculated on the normalized value between FSR reading from right leg and left leg. The result shown based on the real time simulation environment by using Webots Robotic Software. A simulation result shows that a NAO humanoid robot successfully walks in stable condition by following five different walking parameter setting. The humanoid robot is stable if and only if the normalized value of the ZMP is between 1 and -1.